Could the advancement of internet contribute to price harmonization? - Yapp, Emily Hon Tshin; Lee, Hock-Ann (International Academy of Business and Ecomomics, 2006)
This paper is a combination of electronic marketing about price harmonisation and international economics. It has been conducted to examine the impact of the internet on price harmonisation. Eight East Asian economics data namely; Hong Kong, Indonesia, Japan, Korea, Malaysia, the Philippines, Singapore and Thailand had been selected. The data are then divided into two different sample periods which are the Pre-Internet Age period (October 1980 – December 1989); and the Internet and Wireless Age period (January 1990 – December 2005). To investigate price harmonisation, the theory of international economics, namely purchasing power parity has been used. It is found that there is no evidence of price harmonisation during the Pre-Internet Age period as well as the Internet and Wireless Age period. The major implication of this study is that pricing strategies are the important element in marketing as a whole.